Ni3S4 / NiFe-LDH / IF heterojunction catalyst as well as preparation method and application thereof

By using the corrosion reaction of nickel chloride and sodium thiosulfate on the foamed iron substrate, Ni3S4/NiFe-LDH heterojunction catalyst is generated, which solves the complex and high cost of preparation process of electrolytic water redox catalysts, and realizes the normal temperature It is highly efficiently prepared with high-active catalysts, suitable for industrial high current density applications, and significantly improves the stability and specific surface area of ​​the catalyst.

CN119194500APending Publication Date: 2024-12-27HUAZHONG UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411342243.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing electrolytic water redox catalyst preparation process is complex and costly, making it difficult to apply under high industrial current density, and the traditional method has a high reaction temperature and a long time, which cannot meet the industrial needs.

Method used

Using iron foam as the substrate, the corrosion reaction is carried out through a mixed solution of nickel chloride and sodium thiosulfate to rapidly generate Ni3S4/NiFe-LDH heterojunction catalyst at room temperature, using the combined action of chloride ions and thiosulfate ions. Form a three-dimensional nanoflower-like corrosion layer to improve the activity and stability of the catalyst.

Benefits of technology

It realizes the rapid preparation of high-active and stable electrolytic oxygen-induced catalysts at room temperature, solves the problem of easy catalyst falling off at high current density, reduces raw material costs and reaction time, has industrial application potential, and performs under high current density. Excellent redox performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194500A_ABST
    Figure CN119194500A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst preparation, and particularly relates to a Ni3S4 / NiFe-LDH / IF heterojunction catalyst as well as a preparation method and application thereof. The preparation method comprises the following steps: after carrying out cleaning pretreatment on foam iron, putting the foam iron into a mixed aqueous solution of nickel chloride and sodium thiosulfate to carry out corrosion reaction, and after the reaction is finished, washing and drying to obtain the Ni3S4 / NiFe-LDH / IF catalyst. The Ni3S4 / NiFe-LDH heterojunction electrolysis water oxygen evolution catalyst is grown on the foam iron substrate through in-situ corrosion by combining corrosion engineering and a heterojunction construction strategy. The material prepared by the method is simple in process, convenient and fast, under the combined action of chloride ions and thiosulfate ions, the water electrolysis oxygen evolution heterostructure catalyst with the three-dimensional nano flower-shaped morphology and good performance can be rapidly generated only at the normal temperature, the specific surface area is effectively increased, meanwhile, many active sites are exposed, and the preparation method is suitable for large-scale industrial production. The activity and the stability of the catalyst are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to a Ni3S4 / NiFe-LDH / IF heterojunction catalyst and a preparation method and application thereof. Background Art

[0002] With the intensification of the energy crisis and the deterioration of the environment, it has become a consensus among mankind to change the traditional energy structure and increase the proportion of hydrogen energy. Hydrogen energy is a secondary energy source with abundant sources, green and low carbon, and wide application. It can not only be applied to many industrial fields, such as oil refining, steel smelting and fertilizer manufacturing, but also can be used to prepare some fine chemicals. It is an important industrial raw material with high demand and wide application. However, the gray hydrogen produced by traditional fossil fuel hydrogen production not only has impurities but also is accompanied by a large amount of toxic waste, leading to environmental deterioration. Therefore, the development of green hydrogen production technology is an important means to alleviate the energy crisis and curb environmental pollution.

[0003] Hydrogen production by water electrolysis has become one of the important ways to prepare "green hydrogen" due to its environmental friendliness and pure hydrogen advantages. At the anode of water electrolysis, the oxygen evolution reaction (OER) catalyst can significantly reduce the energy required for the reaction, break through the kinetic barriers in the water electrolysis process, and thus achieve a significant improvement in the overall efficiency of water electrolysis. At present, commonly used commercial water electrolysis OER catalysts such as ruthenium dioxide or iridium dioxide have high catalytic activity but have problems such as high prices. Among many non-precious metal catalysts, NiFe-LDH has the advantages of low cost and high OER activity, making it one of the most active materials for the anode reaction of water electrolysis. However, this type of hydrotalcite material usually needs to be prepared by cumbersome and rigorous heat treatment methods such as hydrothermal and solvothermal methods, which hinders its large-scale application in industry.

[0004] Corrosion engineering is a promising technology for preparing efficient electrocatalysts by using the self-corrosion reaction of metal materials. Metal substrates can be corroded by some strong corrosive agents to produce metal ions, which coordinate with hydroxyl or other electronegative free radicals to form precipitates. After the corrosion reaction, a nanosheet-like corrosion layer is formed on the metal surface, which can be used as an OER active material. The self-supporting catalyst prepared by this strategy is not only simple in method, but also highly flexible and extremely low in cost. At the same time, constructing heterojunction materials is one of the most effective ways to increase the active sites of catalysts. The fully exposed heterojunction interface is conducive to promoting the interaction between different components, optimizing the electronic structure and thus increasing the OER catalytic activity.

[0005] Patent CN114774977A discloses a sulfur-doped nickel hydroxide-cerium dioxide composite nanorod array electrocatalyst, preparation method and application thereof, wherein nickel nitrate, cerium nitrate and sodium thiosulfate are used as precursors, and sulfur-doped nickel hydroxide-cerium dioxide composite nanorod array is in situ grown on a nickel foam substrate by a one-step hydrothermal method. Its electrocatalytic performance is improved, but the reaction temperature is high, the time is long, and it still cannot meet the requirements of industrial high current density.

[0006] Therefore, it is necessary to provide a method for preparing a Ni3S4 / NiFe-LDH / IF heterojunction catalyst to solve the above problems. Summary of the invention

[0007] The object of the present invention is to provide a Ni3S4 / NiFe-LDH / IF heterojunction catalyst and a preparation method and application thereof, so as to quickly prepare a catalyst with high activity and stability under mild reaction conditions.

[0008] To achieve the above-mentioned purpose, the present invention provides a method for preparing a Ni3S4 / NiFe-LDH / IF heterojunction catalyst, comprising: placing cleaned foamed iron into a mixed aqueous solution of nickel chloride and sodium thiosulfate for corrosion reaction, washing and drying after the reaction is completed, and obtaining a Ni3S4 and NiFe-LDH heterojunction catalyst loaded on the foamed iron.

[0009] Furthermore, the concentration of nickel chloride in the mixed aqueous solution is 0.05-0.2 mol / L, and the concentration of sodium thiosulfate is 0.01-0.05 mol / L. Preferably, nickel chloride hexahydrate and sodium thiosulfate pentahydrate are used.

[0010] Furthermore, the size of the foamed iron is (1-3) cm×(1-3) cm, the thickness is 1-3 mm, and the amount of the mixed aqueous solution is 30-80 mL.

[0011] Furthermore, the temperature of the corrosion reaction is 10-40° C., preferably 20-30° C., and the time is 0.5-3 h, preferably 0.5-1.5 h.

[0012] Furthermore, the cleaning pretreatment is to use anhydrous ethanol, hydrochloric acid and deionized water ultrasonic cleaning in sequence, and then dry.

[0013] Furthermore, the concentration of the hydrochloric acid is 1 to 3 mol / L.

[0014] The present invention also provides a Ni3S4 / NiFe-LDH / IF heterojunction catalyst, which is prepared by any of the preparation methods described above.

[0015] Furthermore, the Ni3S4 / NiFe-LDH / IF heterojunction catalyst is used for water electrolysis reaction.

[0016] Furthermore, the water electrolysis reaction is a three-electrode alkaline water electrolysis system or an anion exchange membrane electrolyzer system, and the Ni3S4 / NiFe-LDH / IF heterojunction catalysts are all used as anodes.

[0017] Furthermore, the electrolyte of the three-electrode alkaline water electrolysis system is 1 mol / L KOH, and the electrolyte in the anion exchange membrane electrolyzer system is 1 mol / L KOH or pure water.

[0018] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0019] 1. The present invention combines corrosion engineering and heterogeneous structure construction strategies, and directly puts the cleaned foamed iron into a mixed solution of nickel chloride and sodium thiosulfate to carry out metal self-corrosion reaction. Under the joint action of chloride ions and thiosulfate ions, a heterogeneous structure catalyst for oxygen evolution by electrolysis of water with good performance can be quickly generated at room temperature. The corrosion layer grown in situ on the surface of the foamed iron presents a three-dimensional nanoflower-like morphology, which is beneficial to optimizing the electronic structure. It not only effectively increases the specific surface area, but also exposes more active sites, thereby improving the activity and stability of the catalyst and further improving the oxygen evolution performance.

[0020] 2. The self-supporting catalyst prepared by the present invention using foamed iron as the substrate not only solves the problem that the powdered catalyst is easy to fall off under high current density, but also the foamed iron will release a large amount of iron ions under the action of corrosion, which can directly serve as an iron source. This simple, convenient and low-cost process preparation method has certain potential for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 X-ray diffraction (XRD) diagrams of the materials prepared in Example 1 and Comparative Examples 1 and 2;

[0022] Figure 2 The Raman spectra of the materials prepared in Example 1 and Comparative Examples 1 and 2 are shown;

[0023] Figure 3 The scanning electron microscope (SEM) images of the materials prepared in Example 1 and Comparative Examples 1 and 2 are shown;

[0024] Figure 4 This is a transmission electron microscope (TEM) image of the material prepared in Example 1;

[0025] Figure 5 This is a surface scanning energy spectrum mapping image (Mapping) of the material prepared in Example 1;

[0026] Figure 6 This is an atomic force microscope (AFM) image of the material prepared in Example 1;

[0027] Figure 7 The linear polarization curves (LSV) of the OER of the materials prepared in Example 1 and Comparative Examples 1 and 2 in an oxygen-saturated 1M KOH electrolyte;

[0028] Figure 8 100h chronoamperometric curve of OER of the material prepared in Example 1 in an oxygen-saturated 1M KOH electrolyte;

[0029] Fig. 9 This is a performance curve of an anion exchange membrane (AEM) electrolyzer in 1M KOH electrolyte or pure water for the material prepared in Example 1. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0031] Most of the existing water electrolysis catalysts cannot be used at industrial high current densities (≥500mA cm -2 ) application, and the use of expensive precious metals as raw materials for catalysts. The present invention provides a Ni3S4 / NiFe-LDH / IF heterojunction catalyst, with foamed iron (IF) as a substrate, and the corrosion layer on the foamed iron is composed of two physical phases of Ni3S4 and NiFe-LDH with good crystallinity. The foamed iron is placed in a mixed solution of nickel chloride and sodium thiosulfate, and a Ni3S4 / NiFe-LDH heterojunction electrolytic water oxygen evolution catalyst can be quickly grown on the foamed iron substrate by in-situ corrosion at room temperature and pressure. The present invention in-situ grows a Ni3S4 / NiFe-LDH heterojunction catalyst on a foamed iron substrate for an anode reaction of electrolyzed water. Inspired by the fact that iron is easily corroded in nature, the foamed iron is used as a catalyst substrate, and chloride ions in nickel salts are used to accelerate the corrosion of iron, which can not only reduce the cost of raw materials and shorten the reaction time, but also further promote the formation of hydroxide / sulfide two-phase substances. At the same time, the reaction is carried out under normal temperature and pressure conditions, which reduces the difficulty of the material preparation process and is conducive to industrial-scale production.

[0032] The specific steps are as follows:

[0033] (1) The foamed iron was ultrasonically cleaned with anhydrous ethanol, hydrochloric acid and deionized water for 15 min in sequence, and then vacuum dried;

[0034] (2) The pretreated foamed iron is placed in a mixed aqueous solution of nickel chloride hexahydrate and sodium thiosulfate pentahydrate and stirred to cause a corrosion reaction. After the reaction is completed, it is washed three times with deionized water and ethanol in sequence, and then vacuum dried to obtain a Ni3S4 / NiFe-LDH / IF catalyst.

[0035] The present invention combines corrosion engineering and heterojunction construction strategies to in-situ corrode and grow a Ni3S4 / NiFe-LDH heterojunction water electrolysis oxygen evolution catalyst on a foamed iron substrate. The material process prepared by this method is simple, convenient and fast. Under the joint action of chloride ions and thiosulfate ions, a heterostructure catalyst for water electrolysis oxygen evolution with good performance can be quickly generated at room temperature. The corrosion layer grown in situ on the surface of the foamed iron presents a three-dimensional nano-flower-like morphology, which not only effectively increases the specific surface area, but also exposes more active sites, thereby improving the activity and stability of the catalyst.

[0036] Example 1

[0037] A method for preparing a self-supporting Ni3S4 / NiFe-LDH / IF heterojunction catalyst, the specific steps are as follows:

[0038] (1) The foamed iron was cut into a size of 2 cm × 2 cm, and ultrasonically cleaned with anhydrous ethanol, 2 mol / L hydrochloric acid, and deionized water for 15 min, respectively, and then dried in a vacuum drying oven at 60°C for 12 h to obtain clean foamed iron.

[0039] (2) The pretreated foamed iron was placed in a mixed solution of 50 mL of nickel chloride hexahydrate (concentration 0.1 M) and sodium thiosulfate pentahydrate (concentration 0.03 M), and stirred at room temperature and pressure for 1 h.

[0040] (3) The foamed iron after the reaction was taken out, washed with deionized water and anhydrous ethanol for three times respectively, and vacuum dried at 60° C. for 12 h to obtain the Ni 3 S 4 / NiFe-LDH / IF catalyst.

[0041] Comparative Example 1

[0042] The difference from Example 1 is that in this comparative example, nickel chloride hexahydrate is not added, and the pretreated foamed iron is directly placed in 50 mL of sodium thiosulfate pentahydrate (concentration of 0.03 M) solution to obtain S-FeOOH / IF catalyst.

[0043] Comparative Example 2

[0044] The difference from Example 1 is that in this comparative example, sodium thiosulfate pentahydrate is not added, and the pretreated foamed iron is directly placed in 50 mL of hydrated nickel chloride (concentration of 0.1 mol / L) solution to obtain a NiFe-LDH / IF catalyst.

[0045] Example 2

[0046] A method for preparing a self-supporting Ni3S4 / NiFe-LDH / IF heterojunction catalyst, the specific steps are as follows:

[0047] (1) The foamed iron was cut into a size of 2 cm × 2 cm, and ultrasonically cleaned with anhydrous ethanol, 2 mol / L hydrochloric acid, and deionized water for 15 min, respectively, and then dried in a vacuum drying oven at 60°C for 12 h to obtain clean foamed iron.

[0048] (2) The pretreated foamed iron was placed in a mixed solution of 50 mL of nickel chloride hexahydrate (concentration of 0.1 mol / L) and sodium thiosulfate pentahydrate (concentration of 0.01 mol / L), and stirred at room temperature and pressure for 1 hour.

[0049] (3) The foamed iron after the reaction was taken out, washed with deionized water and anhydrous ethanol for three times respectively, and dried in vacuum at 60° C. for 12 h to obtain the Ni 3 S 4 / NiFe-LDH / IF-0.01M catalyst.

[0050] Example 3

[0051] A method for preparing a self-supporting Ni3S4 / NiFe-LDH / IF heterojunction catalyst, the specific steps are as follows:

[0052] (1) The foamed iron was cut into a size of 2 cm × 2 cm, and ultrasonically cleaned with anhydrous ethanol, 2 mol / L hydrochloric acid, and deionized water for 15 min, respectively, and then dried in a vacuum drying oven at 60°C for 12 h to obtain clean foamed iron.

[0053] (2) The pretreated foamed iron was placed in a mixed solution of 50 mL of nickel chloride hexahydrate (concentration of 0.1 mol / L) and sodium thiosulfate pentahydrate (concentration of 0.03 mol / L), and stirred at room temperature and pressure for 0.5 h.

[0054] (3) The foamed iron after the reaction was taken out, washed with deionized water and anhydrous ethanol for three times respectively, and dried under vacuum at 60° C. for 12 h to obtain the Ni 3 S 4 / NiFe-LDH / IF-0.5h catalyst.

[0055] Example 4

[0056] A method for preparing a self-supporting Ni3S4 / NiFe-LDH / IF heterojunction catalyst, the specific steps are as follows:

[0057] (1) The foamed iron was cut into a size of 2 cm × 2 cm, and ultrasonically cleaned with anhydrous ethanol, 2 mol / L hydrochloric acid, and deionized water for 15 min, respectively, and then dried in a vacuum drying oven at 60 °C for 12 h to obtain clean foamed iron.

[0058] (2) The pretreated foamed iron was placed in a mixed solution of 50 mL of nickel chloride hexahydrate (concentration of 0.1 mol / L) and sodium thiosulfate pentahydrate (concentration of 0.05 mol / L), and stirred at room temperature and pressure for 1 h.

[0059] (3) The foamed iron after the reaction was taken out, washed with deionized water and anhydrous ethanol for three times respectively, and dried under vacuum at 60° C. for 12 h to obtain the Ni 3 S 4 / NiFe-LDH / IF-0.05M catalyst.

[0060] Example 5

[0061] A method for preparing a self-supporting Ni3S4 / NiFe-LDH / IF heterojunction catalyst, the specific steps are as follows:

[0062] (1) The foamed iron was cut into a size of 2 cm × 2 cm, and ultrasonically cleaned with anhydrous ethanol, 2 mol / L hydrochloric acid, and deionized water for 15 min, respectively, and then dried in a vacuum drying oven at 60 °C for 12 h to obtain clean foamed iron.

[0063] (2) The pretreated foamed iron was placed in a mixed solution of 50 mL of nickel chloride hexahydrate (concentration of 0.1 mol / L) and sodium thiosulfate pentahydrate (concentration of 0.03 mol / L), and stirred at room temperature and pressure for 1.5 h.

[0064] (3) The foamed iron after the reaction was taken out, washed with deionized water and anhydrous ethanol for three times respectively, and dried under vacuum at 60° C. for 12 h to obtain the Ni 3 S 4 / NiFe-LDH / IF-1.5h catalyst.

[0065] The XRD patterns of the materials prepared in Example 1 and Comparative Examples 1 and 2 are as follows: Figure 1As shown in the figure, it can be seen that the diffraction peaks formed can correspond well to the standard card. Specifically, the sample with only Na2S2O3·5H2O reaction formed a typical orthorhombic FeOOH phase, and the diffraction peaks at 14.1°, 27.0°, 29.9°, 36.3°, 46.9°, 52.7° and 60.7° correspond to the (200), (210), (101), (301), (020), (511) and (321) crystal planes of FeOOH, respectively. The sample with only NiCl2·6H2O added formed NiFe-LDH after corrosion reaction, and the diffraction peaks at 11.5°, 23.3°, 34.6°, 39.0°, 46.4°, 60.3°, 61.3° and 65.2° correspond to its (003), (006), (012)(015), (018), (110), (113) and (116) crystal planes, respectively. The sample with NiCl2·6H2O and Na2S2O3·5H2O added not only had the diffraction peaks of NiFe-LDH, but also some peaks at 31.3°, 37.9°, 49.9° and 54.7°, which correspond to its (311), (400), (511) and (440) crystal planes, respectively. The results show that NiCl2·6H2O and Na2S2O3·5H2O will spontaneously generate heterostructures of Ni3S4 and NiFe-LDH after reacting with foamed iron at room temperature. This heterostructure will expose more abundant active sites, which is conducive to the enhancement of electrochemical activity.

[0066] The Raman spectra of the materials prepared in Example 1 and Comparative Examples 1 and 2 are as follows: Figure 2 As shown, all samples were -1 Intensity peaks appeared at 468 cm / s, which can be attributed to the Fe-O vibration in disordered FeOOH. In contrast, S-FeOOH / IF showed the strongest peak intensity, indicating that it contained the most FeOOH phase. NiFe-LDH / IF and Ni3S4 / NiFe-LDH / IF showed strong peaks at 468 cm / s. -1 and 541cm -1 The stretching vibrations of δ(Ni-O) and ν(Ni-O) in Ni(OH)2 appeared. In addition, Ni3S4 / NiFe-LDH / IF showed a -1 and 276cm -1 Additional Raman bands are shown, which are attributed to the vibration of Ni-S in Ni3S4.

[0067] The SEM images of the materials prepared in Example 1 and Comparative Examples 1 and 2 are as follows: Figure 3As shown in the figure, it can be observed that the S-FeOOH / IF catalyst is composed of irregular sheet structures, which are densely distributed on the surface of the foam iron substrate to form a covering layer. The SEM image of NiFe-LDH / IF shows that after 1 hour of reaction, the foam iron surface shows a more dense nanosheet structure than S-FeOOH / IF. The SEM image of the heterogeneous structure catalyst Ni3S4 / NiFe-LDH / IF shows a more uniform distribution of the grown nanosheet structures compared to S-FeOOH / IF and NiFe-LDH / IF. By zooming in, it can be more clearly observed that a flower-like nanosheet array with an average size of 500nm is uniformly grown on the IF substrate. Each of these dense nanosheet structures is independent and interconnected to form an interpenetrating network. This structure not only increases the specific surface area of ​​the material, but also provides more active sites, allowing reactants to more easily contact the active centers of the catalyst.

[0068] TEM of Example 1 Figure 4 As shown in the figure, it can be clearly observed that the material presents a nanosheet structure, and each nanosheet overlaps to form a 3D flower-like morphology. Under high-power transmission electron microscopy (HRTEM), it can be clearly observed that the lattice fringes of 0.260nm correspond to the (012) crystal plane of NiFe-LDH, while the lattice spacings of 0.285nm, 0.182nm and 0.237nm correspond to the (311), (511) and (400) crystal planes of Ni3S4, respectively.

[0069] The energy spectrum mapping image of Example 1 is as follows Figure 5 As shown in the figure, it is clearly shown that Ni, Fe, O, S and Cl elements exist in the catalyst and are evenly distributed on the surface of the sample. - The corrosion of Ni3S4 / NiFe-LDH formed an in-situ corrosion layer on the foamed iron.

[0070] The AFM image of Example 1 is as follows Figure 6 As shown in the figure, it can be clearly observed that the average thickness of the nanosheets is about 3.88 nm. This thinner nanosheet structure can significantly promote the exposure of more active substances, thereby enhancing the electrocatalytic activity.

[0071] The electrochemical performance of OER of the catalysts prepared in Example 1 and Comparative Examples 1 and 2 was tested. The test method was as follows: the material was cut into a size of 0.25 cm × 0.25 cm, and then fixed on a platinum electrode clamp as a working electrode, a mercury / mercury oxide electrode as a reference electrode, a graphite rod as a counter electrode and an oxygen-saturated 1M KOH to form a three-electrode system electrolytic cell. The catalyst was first activated by cyclic voltammetry (CV) with a scanning potential window of 1.0 to 1.7 V (vs. RHE) and a scanning rate of 0.1 V / s; then the potential-current curve was recorded using linear scanning voltammetry at a scanning rate of 5 mV / s. The test results are shown in Figure 2. Figure 7 As shown in the figure, it can be seen that the OER performance of Example 1 is the best in 1M KOH electrolyte, at 200mA cm -2 The overpotential at a current density of only 250 mV is even lower at 500 mA cm -2 The overpotential at high current density is 297mV.

[0072] The catalyst prepared in Example 1 was tested for OER stability. The test method was as follows: the material was cut into a size of 0.25 cm × 0.25 cm, and then fixed on a platinum electrode clamp as a working electrode, a mercury / mercuric oxide electrode as a reference electrode, a graphite rod as a counter electrode and a 1M KOH electrolyte to form a three-electrode system electrolytic cell. The catalyst was first activated by CV at a scan rate of 0.1 V / s; then the time-current density curve was recorded by chronoamperometry. The test results are shown in Figure 2. Figure 8 As shown, in 1 M KOH solution, the potential retention rate was 96% after 100 h of OER test.

[0073] The catalyst prepared in Example 1 was used to test the performance of an anion exchange membrane electrolyzer. The test method was as follows: a 2cm×2cm self-supporting Pt / C / IF material and a 2cm×2cm material prepared in Example 1 were fixed at both ends of the anion exchange membrane as the cathode and anode. The anion exchange membrane used a 35μm thick PAP-TP-85 material, and the foamed iron itself served as the gas diffusion layer at the anode and cathode ends. In the AEMWE experiment, 1M KOH or ultrapure water was added at 3mL min -1 The current density of the electrolytic cell was gradually increased from 0 to 500 mA cm -2 The cell voltage was measured while the current density was gradually increased for activation, and polarization curves were recorded at room temperature (25°C), 40°C, 60°C and 80°C.

[0074] The test results are as follows Fig. 9As shown in the figure, it can be clearly observed that the performance of Example 1 is better than that of commercial IrO2 in 1M KOH electrolyte. Specifically, only 1.63V is required to achieve 1A cm at 80°C. -2 The current density of 1.5V / cm2 was 450, 566, 684 and 864 mA cm2 at 25, 40, 60 and 80 °C, respectively, indicating that it weakened the kinetic energy barrier of the overall water electrolysis at the anode and increased the advantage of catalytic performance. -2 The current density reflects the performance of the catalyst under extreme conditions and further highlights its intrinsic catalytic activity.

[0075] In summary, under the combined action of chloride ions and thiosulfate ions, the present invention can quickly generate a water electrolysis oxygen evolution heterogeneous structure catalyst with good performance at room temperature. The corrosion layer grown in situ on the surface of the foamed iron presents a three-dimensional nanoflower morphology, which not only effectively increases the specific surface area, but also exposes more active sites, thereby improving the activity and stability of the catalyst. When used as the anode in the water electrolysis oxygen evolution catalyst, at 500mA cm -2 The overpotential at the industrial current density is only 297mV, and the stability retention rate is 96% after 100h operation. When used as the anode of an anion exchange membrane electrolyzer, only 1.86V of cell voltage is needed in pure water medium to drive 1A cm -2 of current density.

[0076] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a Ni3S4 / NiFe-LDH / IF heterojunction catalyst, characterized in that: include: The cleaned foamed iron is placed in a mixed aqueous solution of nickel chloride and sodium thiosulfate for corrosion reaction, and after the reaction is completed, it is washed and dried to obtain Ni3S4 and NiFe-LDH heterojunction catalysts loaded on the foamed iron.

2. The method for preparing the Ni3S4 / NiFe-LDH / IF heterojunction catalyst according to claim 1, characterized in that: The concentration of nickel chloride in the mixed aqueous solution is 0.05-0.2 mol / L, and the concentration of sodium thiosulfate is 0.01-0.05 mol / L.

3. The method for preparing the Ni3S4 / NiFe-LDH / IF heterojunction catalyst according to claim 1, characterized in that: The cross-sectional dimensions of the foamed iron are (1-3) cm×(1-3) cm, and the thickness is 1-3 mm.

4. The method for preparing the Ni3S4 / NiFe-LDH / IF heterojunction catalyst according to claim 1, characterized in that: The temperature of the corrosion reaction is 10-40° C., preferably 20-30° C., and the time is 0.5-3 h, preferably 0.5-1.5 h.

5. The method for preparing the Ni3S4 / NiFe-LDH / IF heterojunction catalyst according to claim 1, characterized in that: The foamed iron is cleaned by ultrasonic cleaning with anhydrous ethanol, hydrochloric acid and deionized water in sequence, and then dried.

6. The method for preparing the Ni3S4 / NiFe-LDH / IF heterojunction catalyst according to claim 5, characterized in that: The concentration of the hydrochloric acid is 1-3 mol / L.

7. A Ni3S4 / NiFe-LDH / IF heterojunction catalyst, characterized in that: The preparation method is described in any one of claims 1 to 6.

8. The use of the Ni3S4 / NiFe-LDH / IF heterojunction catalyst according to claim 7, characterized in that: The Ni3S4 / NiFe-LDH / IF heterojunction catalyst is used for water electrolysis reaction.

9. The use of the Ni3S4 / NiFe-LDH / IF heterojunction catalyst according to claim 8, characterized in that: The water electrolysis reaction is a three-electrode alkaline water electrolysis system or an anion exchange membrane electrolyzer system, and the Ni3S4 / NiFe-LDH / IF heterojunction catalysts are all used as anodes.

10. The use of the Ni3S4 / NiFe-LDH / IF heterojunction catalyst according to claim 9, characterized in that: The electrolyte of the three-electrode alkaline water electrolysis system is 1 mol / L KOH, and the electrolyte in the anion exchange membrane electrolyzer system is 1 mol / L KOH or pure water.

Citation Information

Cited By

  • Nickel sulfide self-supporting water electrolysis electrode in-situ construction method adapting to fluctuating working conditions

    CN122105462A